2014
DOI: 10.3852/13-197
|View full text |Cite
|
Sign up to set email alerts
|

The host ranges of conifer-associated Tricholoma matsutake, Fagaceae-associated T. bakamatsutake and T. fulvocastaneum are wider in vitro than in nature

Abstract: Tricholoma matsutake is the most commercially important edible mushroom in pine forests in Japan. Tricholoma bakamatsutake and T. fulvocastaneum, species closely related to T. matsutake, occur in Fagaceae forests. We examined ectomycorrhizal (EM) formation by these Tricholoma species by in vitro synthesis among seven strains (two of T. matsutake, four of T. bakamatsutake, one of T. fulvocastaneum) and axenic plants of pine (Pinus densiflora) and oak (Quercus serrata, Q. phillyraeoides). All strains, except for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…To carry out axenic dual cultivation, we used a pumiceous soil substrate (hereinafter termed "substrate") that allowed mycorrhizal synthesis between T. matsutake and P. densiflora over a four-month incubation period (Yamanaka et al 2012(Yamanaka et al , 2014. Pumiceous soil (Yamanaka et al 2012(Yamanaka et al , 2014 was chosen in preference to a granitebased substrate (Murata et al 2013b(Murata et al , 2014a(Murata et al , 2014b for the following reason: root systems grown in pumiceous soil can be easily and completely cleaned merely by washing with tap water followed by removal of residual soil particles using forceps, whereas roots grown in granitebased soil must be meticulously brushed in water under a dissecting microscope. The substrate was prepared by adding 160 mL of Hamada medium as modified by Yamanaka et al (2012Yamanaka et al ( , 2014 to contain 1% glucose, 0.5% yeast extract, and 0.25% FeCl 3 ·6H 2 O to 400 mL of dried pumiceous soil (particle diameter ca.…”
Section: Substrates For Dual Cultivation Experimentsmentioning
confidence: 99%
“…To carry out axenic dual cultivation, we used a pumiceous soil substrate (hereinafter termed "substrate") that allowed mycorrhizal synthesis between T. matsutake and P. densiflora over a four-month incubation period (Yamanaka et al 2012(Yamanaka et al , 2014. Pumiceous soil (Yamanaka et al 2012(Yamanaka et al , 2014 was chosen in preference to a granitebased substrate (Murata et al 2013b(Murata et al , 2014a(Murata et al , 2014b for the following reason: root systems grown in pumiceous soil can be easily and completely cleaned merely by washing with tap water followed by removal of residual soil particles using forceps, whereas roots grown in granitebased soil must be meticulously brushed in water under a dissecting microscope. The substrate was prepared by adding 160 mL of Hamada medium as modified by Yamanaka et al (2012Yamanaka et al ( , 2014 to contain 1% glucose, 0.5% yeast extract, and 0.25% FeCl 3 ·6H 2 O to 400 mL of dried pumiceous soil (particle diameter ca.…”
Section: Substrates For Dual Cultivation Experimentsmentioning
confidence: 99%
“…"Artificial" substrates with either agar media covered by clay beads, vermiculite, or vermiculite mixed with andosol and pine bark powder have yielded only Hartig nets with very thin or no fungal sheaths (Guerin-Laguette et al 2004;Vaario et al 2010;Yamada et al 1999b). Yamanaka et al (2014) reported that the symbiont formed ectomycorrhizas with Quercus serrata and Quercus phillyraeoides (Fagaceae) inhabiting low-altitude/temperate climate areas in Japan and with natural hosts of its close relatives Tricholoma bakamatsutake and Tricholoma fulvocastaneum in a substrate containing 2 % glucose, a rather high sugar concentration that often allows ectomycorrhizal formation between unusual plant-microbe combinations (Duddridge 1986a, b). In fact, Yamada et al (2014) documented that ectomycorrhizas were not synthesized between T. matsutake and either Q. serrata or Q. phillyraeoides in a granite-based soil substrate with 0.2 % glucose.…”
Section: Discussionmentioning
confidence: 98%
“…Thin fungal hyphae penetrate the intercellular spaces of the root cortex, develop Hartig net structures and, in P. densiflora, establish a rhizospheric mycelial aggregate, or "shiro", that is required for fruiting in nature (Masui 1927;Yamada et al 1999aYamada et al , b, 2006. In vitro, shiros, which form in granite-based soil substrates, promote growth of P. densiflora and other species not regarded as hosts in nature (Murata et al 2013Yamada et al 2006;Yamanaka et al 2014). Recently, T. matsutake was proven to associate with Tsuga diversifolia (>1600 m a.s.l.)…”
Section: Introductionmentioning
confidence: 98%
“…Morgan, and Sarcodon aspratus (Berk.) S. Ito have never been targeted for cultivation efforts in western countries because their use is unique to Japanese, and in some cases other Asian cuisines (Fangfuk et al, 2010a;Kobayashi, 2005;Masuno et al, 2016;Murakami, 2004;Obana and Yamada, 2012;Ogawa, 1992;Yamanaka et al, 2014). For example, S. aspratus is also quite popular in Korea and China (Marcotullio, 2011) and Astraeus spp.…”
Section: Cultivation Trials With Other Mushroomsmentioning
confidence: 99%